Level of and Factors Determining Physical Activity in Students in Ukraine and the Visegrad Countries - Bergier, Józef; Tsos, Anatolii; Popovych, Dariya; Bergier, Barbara; Niźnikowska, Ewelina; Ács, Pongrác; Junger, Jan; Salonna, Ferdinand (International journal of environmental research and public health, 2018)
Background: Examining the level of physical activity in students is a vital issue as these young people are the future social elite. Methods: The research was conducted in the years 2013⁻2016 and comprised 5008 males and females, mean age of 20.5 ± 2.1 years, including 2237 (55.3%) students from students from Eastern European National University, Lutsk, and Ternopil State Medical University, Ukraine, as well as 2237 (44.7%) from the Visegrad countries, i.e., University of Pécs in Hungary, University in Kosice, Slovakia, University of Olomunec in the Czech Republic and the State School of Higher Education in Biała Podlaska, Poland. It applied a diagnostic survey-the extended version of the International Physical Activity Questionnaire (IPAQ), supplemented with original questions regarding body weight, height, self-assessment of physical fitness and amount of leisure time. Results: The comparison of students' PA from selected European countries, members of the Visegrad group and Ukraine, is particularly vital to the latter country as it demonstrates a different level of socio-economic development. There was noted a significantly higher level of physical activity in students from the Visegrad countries than in Ukraine. Further, there was an overall lower level of physical activity in females compared to males. What was positive about the studied samples was a healthy BMI index in the majority of the male and female respondents, with a significantly higher indicator in Ukraine. Conclusions: Among the factors significantly affecting higher physical activity in both researched samples were the BMI and high self-assessment of physical fitness. There was no significant variation in the level of physical activity and the amount of leisure time, both in those studying in the Visegrad states and Ukraine.
Keywords: BMI; students; Students; zdravotnické přehledy; Female; mladý dospělý; ženské pohlaví; Ukrajina; Adolescent; Slovakia; lidé; cvičení; Ukraine; Humans; Sex Factors; self-assessment of physical fitness; physical activity; Male; gender; sexuální faktory; Czech Republic; Young Adult; Hungary; Česká republika; leisure time; Universities; Slovenská republika; IPAQ; studenti; mužské pohlaví; Health Surveys; Maďarsko; Poland; Exercise; univerzity; mladiství; Polsko